Beliefs and perception about mental health issues: a meta-synthesis - Choudhry FR; Mani V; Ming LC; Khan TM (Neuropsychiatric Disease and Treatment)
Fahad Riaz Choudhry,1 Vasudevan Mani,2 Long Chiau Ming,3,4 Tahir Mehmood Khan5 1Psychology Department, Jeffrey Cheah School of Medicine and Health Sciences, Monash University Malaysia, Sunway City, Selangor, Malaysia; 2College of Pharmacy, Qassim University, Buraidah, Al-Qassim, Kingdom of Saudi Arabia; 3Vector-borne Diseases Research Group (VERDI), Pharmaceutical and Life Sciences CoRe, Universiti Teknologi MARA, Shah Alam; 4Brain Degeneration and Therapeutics Group, Faculty of Pharmacy, Universiti Teknologi MARA, Puncak Alam, 5School of Pharmacy, Monash University Malaysia, Sunway City, Selangor, Malaysia Background: Mental health literacy is the beliefs and knowledge about mental health issues and their remedies. Attitudes and beliefs of lay individuals about mental illness are shaped by personal knowledge about mental illness, knowing and interacting with someone living with mental illness, and cultural stereotypes. Mental health issues are increasing and are alarming in almost every part of the world, and hence compiling this review provides an opportunity to understand the different views regarding mental disorders and problems as well as to fill the gap in the published literature by focusing only on the belief system and perception of mental health problems among general population.Method: The methodology involved a systematic review and the meta-synthesis method, which includes synthesizing published qualitative studies on mental health perception and beliefs.Sample: Fifteen relevant published qualitative and mixed-method studies, regarding the concept of mental health, were identified for meta-synthesis.Analysis: All the themes of the selected studies were further analyzed to give a broader picture of mental health problems and their perceived causes and management. Only qualitative studies, not older than 2010, focusing on beliefs about, attitudes toward, and perceptions of mental health problems, causes, and treatments were included in this review.Results: The findings are divided into four major categories, namely, 1) symptoms of mental health issues, 2) description of mental health issues, 3) perceived causes, and 4) preferred treatment and help-seeking behavior. Each category contains themes and subthemes based on published studies.Conclusion: The findings reveal multiple causes of, descriptions of, and treatment options for mental health problems, thereby providing insight into different help-seeking behaviors. Clarity is offered by highlighting cultural differences and similarities in mental health beliefs and perceptions about the causes of mental health problems. The implications of the studies and recommendations based on current findings are also discussed. Keywords: mental health perception, mental health beliefs, mental health attitudes, meta-synthesis, mental disorders